Bài tập 11 trang 62 Tài liệu dạy – học Toán 8 tập 1

Giải bài tập Rút gọn phân thức

Quảng cáo

Đề bài

Rút gọn phân thức

a) \({{25(x - 2)} \over {20x(2 - x)}}\) ;

b) \({{x{{(4 - x)}^2}} \over {x - 4}}\) ;

c) \({{{{(x - y)}^2}} \over {x{{(y - x)}^3}}}\) ;

d) \({{x(x - 2)} \over {{{(2 - x)}^3}}}\) .

Lời giải chi tiết

\(\eqalign{  & a)\,\,{{25\left( {x - 2} \right)} \over {20x\left( {2 - x} \right)}} = {{25\left( {x - 2} \right)} \over { - 20x\left( {x - 2} \right)}}  \cr  & \,\,\,\,\, = {{5\left[ {5\left( {x - 2} \right)} \right]} \over { - 4x\left[ {5\left( {x - 2} \right)} \right]}} = {5 \over { - 4x}}  \cr  & b)\,\,{{x{{\left( {4 - x} \right)}^2}} \over {x - 4}} = {{x{{\left( {4 - x} \right)}^2}} \over {\left( {4 - x} \right)\left( { - 1} \right)}}  \cr  & \,\,\,\,\, = {{x\left( {4 - x} \right)} \over { - 1}} = {x^2} - 4x  \cr  & c)\,\,{{{{\left( {x - y} \right)}^2}} \over {x{{\left( {y - x} \right)}^3}}} = {{{{\left( {y - x} \right)}^2}} \over {x{{\left( {y - x} \right)}^3}}}  \cr  & \,\,\,\,\, = {{{{\left( {y - x} \right)}^2}} \over {{{\left( {y - x} \right)}^2}\left[ {x\left( {y - x} \right)} \right]}} = {1 \over {x\left( {y - x} \right)}}  \cr  & d)\,\,{{x\left( {x - 2} \right)} \over {{{\left( {2 - x} \right)}^3}}} = {{ - x\left( {2 - x} \right)} \over {{{\left( {2 - x} \right)}^3}}}  \cr  & \,\,\,\,\, = {{ - x\left( {2 - x} \right)} \over {\left( {2 - x} \right){{\left( {2 - x} \right)}^2}}} = {{ - x} \over {{{\left( {2 - x} \right)}^2}}} \cr} \)

Loigiaihay.com

Quảng cáo

Gửi bài